The Impact of Logic (In)Compatibility: Green Investing, State Policy, and Corporate Environmental Performance. (December 2021) - Yan, Shipeng; Almandoz, Juan (John); Ferraro, Fabrizio
Environmental protection is widely perceived as a state responsibility, but market-based solutions such as green investing have emerged in the financial sector. Little research has addressed whether green investing can affect corporate environmental performance and how the state would moderate such an impact. Using an institutional logics perspective, we extend the literature on institutional complexity by exploring the factors leading to compatibility of logics and practices. We theorize that the success of green investing as a novel hybrid practice combining financial means and environmental goals depends on the legitimacy it achieves as an appropriate solution to the stated goal, and this legitimacy can be boosted or dampened by other hybrid practices in the field. Analyzing a panel dataset of 3, 706 firms from 20 countries between 2002 and 2013, we find a positive relationship between the relative size of green investment in the economy and firm-level environmental performance in that country. This relationship is moderated by state policies: a strong environmental protection policy weakens the positive relationship between green investing and corporate environmental performance, and a strong shareholder protection policy strengthens the relationship. We contribute to research on institutional complexity, logic compatibility, and public–private cooperation in pursuing the common good.